2017
DOI: 10.1007/s00125-017-4472-3
|View full text |Cite
|
Sign up to set email alerts
|

Why childhood-onset type 1 diabetes impacts labour market outcomes: a mediation analysis

Abstract: Aims/hypothesis Previous studies show a negative effect of type 1 diabetes on labour market outcomes such as employment and earnings later in life. However, little is known about the mechanisms underlying these effects. This study aims to analyse the mediating role of adult health, education, occupation and family formation. Methods A total of 4179 individuals from the Swedish Childhood Diabetes Register and 16,983 individuals forming a population control group born between 1962 and 1979 were followed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Corresponding general data concerning work incapacity in Sweden in the year 2010 indicated a mean 5.7% prevalence [30]. Earlier studies have mostly addressed the financial aspects of impaired work ability [13,15,16,18]. Additionally, earlier reports often lack direct comparisons with the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding general data concerning work incapacity in Sweden in the year 2010 indicated a mean 5.7% prevalence [30]. Earlier studies have mostly addressed the financial aspects of impaired work ability [13,15,16,18]. Additionally, earlier reports often lack direct comparisons with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, data concerning type 1 diabetes and the relationships between musculoskeletal disorders and work ability are limited [11,12]. Previous comparative reports of work ability in diabetes patients and the general population focus on financial aspects of occupational status rather than possible explanatory factors [16][17][18]. A Danish population-based study reported 12% higher sick leave per year in patients with type 1 diabetes compared with the general population, and additionally impaired HRQOL in type 1 diabetes patients.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of type 1 diabetes is increasing in children and youth, suggesting that environmental factors are influencing those with a genetic predisposition [ 68 ]. Linking the Swedish Child Diabetes Register and socioeconomic data, researchers have studied the association between education, employment, and earnings [ 69 72 ]. Adult type 1 diabetes is associated with employment and salary development [ 73 ].…”
Section: Contents Of Lisamentioning
confidence: 99%
“…Some examples include studies on total costs of care for people with diabetes [7][8][9][10], on prevalence and incidence of diabetes [11,12] and on types of glucoselowering medication and clinical outcomes [13]. Similar topics have also been addressed using patient cohorts registered in quality registers or incidence registers and using outcome data from national health registers in Sweden [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%